Revolutionizing Food Processing: Innovative Sustainable Technologies and Future Opportunities - , Akanksha Sant; , Reshu Rajput; Shubham,; , Shilpa Kaushal (Archives of Current Research International, 2025)
Everyone having access to or not to a sufficient supply of processed, safe, fresh, nutritional and in pocket-friendly food is a significant worldwide issue. By 2050, it could pose a major challenge for feeding 9 billion people, for which increasing food production technologies need to be addressed. Long term enhancement in food processing by reducing losses at every stage of the supply chain, managing the supply chain from production to consumption, including preservation, nutrient content, safety and shelf life. Massive amounts of streaming data, known as big data come under the Internet of Things (IoT). A new technology based platform helps in food production and processing technology by maintaining the big data and its further analysis. This review approaches scope and food production, food processing and its related technologies. Emerging technologies are saving the food supply and making the food economy more sustainable. Furthermore, this review is based on an overview of artificial intelligence, big data and sensors used in the food production sector.